Revealing millimetre-scale ground movements in London using SqueeSAR™ - Bischoff,CA; Ghail,RC; Mason,PJ; Ferretti,A; Davis,JA (Quarterly Journal of Engineering Geology and Hydrogeology, 2020)
A series of illustrated examples is presented here to demonstrate the capabilities of ground-level monitoring using InSAR (interferometric synthetic aperture radar). Greater London is an ideal area to demonstrate and validate measurements derived using InSAR; its continuous urban fabric and the regular acquisition of SAR images from high-resolution sensors, such as TerraSAR-X, allows detection and monitoring of over 1.7million measurement points with millimetre-scale accuracy. The results, some of which are shown here, reveal fascinating spatial and temporal patterns of ground motion across London and demonstrate the benefit of using high-resolution InSAR technologies in engineering applications. Interpreting the motion patterns can be challenging, however, owing to their complex and sometimes mysterious causes; we therefore welcome any assistance in doing so and we hope this photographic feature serves to trigger interest.